IMPACT OF MANGROVE REHABILITION ON COMMUNITY INCOME AT LUBUK KERTANG VILLAGE - Roswita Hafni (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Extensive mangrove forest scattered on several islands in Indonesia amounted to4,251,011 hectares. However, more than half the total area of mangrove forests that haveturned out in a badly damaged condition. The mangrove forests of North Sumatra provincelocated along the east coast with extensive of 199,478.32 hectares. Langkat has the mostextensive mangrove area ie 50,650.93 ha, but since 2006 the mangrove forest has beenconverted into oil palm plantations. Economically natural resources is the source of income isreduced because it will be decreasing livelihoods of fishermen in six villages.The aims of research was to determine of mangrove forests condition, and howmangrove rehabilitation impacts on the income of traditional fishing communities, speciallyon village of Lubuk Kertang Langkat District of West Brandan. This research is descriptiveand the population in this study is the whole area of mangrove forest in the Lubuk Kertang’svillage as many 170 KK of fishermen. The number of samples with as many as 62 kk withslovin techniques. Data analysis technique used is the comparative analyses.The results that: (1). The mangrove forests in the village of Lubuk Kertang with extensivedamage reached 740 ha (61.67%) from the total 1200 ha of existing. Severe damage ofmangrove forest of 528 ha (71.35%). (2). The destruction of mangrove forests negativeimpact on fishermen's income, with significant values of 0.020 <0.05. It is claimed that thereis a correlation between before and after the rehabilitation of mangrove forests. Beforedamage occurs fishing communities adequate income to make ends meet, but after thedamage occurred a huge decline of incomes.